##### Ad

related to: K

**k**-4/9=3 you want to isolate**k**to find the answer, so you have to do the operations in reverse. so**k**-4=3x9**k**-4=27**k**=27+4**k**=313 Answers · Education & Reference · 28/02/2010

Let (x -

**k**) / (x - 1) = y x -**k**= yx - y x = yx - y +**k**x - yx = y +**k**x(1 - y) = y +**k**x = (-y +**k**) / (1 - y) x = (y -**k**) / (y - 1) It would seem that the function is generally its own inverse...2 Answers · Science & Mathematics · 12/08/2010

Depends which Special

**K**you mean....... if your enquiry is in regards to cereal then the...14 Answers · Entertainment & Music · 11/01/2008

**k**^.3 is the same as saying**k**^(3/10)**k**^(3/10) is the same as saying tenth_root(**k**^3)**k**...7 Answers · Science & Mathematics · 04/01/2007

**k**(x) = 2 sin (x+π) / (sin (x+π) - 3) = 2 (- sin x) / (- sin x - 3) = 2 sin x / (sin x + 3) = [2 (sin x + 3) - 6] / (sin x + 3) = 2 - 6 / (sin x + 3) So for**k**^-1(x) we get x = 2 - 6 / (sin**k**^-1(x) + 3) => 6 / (sin**k**^-1(x) + 3) = 2 - x =>...1 Answers · Science & Mathematics · 16/12/2013

**k**(**k**- 5) > 0 in two cases: 1)**k**> 0 and (**k**- 5) > 0 2)**k**< 0 and (**k**- 5) < 0 In case 1,**k**> 0 and**k**> 5; both of these are true when**k**> 5. In case 2,**k**...1 Answers · Science & Mathematics · 11/04/2010

Decomposing 1/[

**k**(**k**+1)(**k**+2)], you have: A/**k**+ B/(**k**+1) + C/(**k**+2) = 1/[**k**(**k**+1.... Therefore: A(**k**+1)(**k**+2) + B(**k**)(**k**+2) + C(**k**)(**k**+1) = 1 which must hold true for all valid values of**k**. To determine...2 Answers · Science & Mathematics · 08/09/2007

Note that Σ(

**k**= 5 to ∞) C(**k**-1,**k**-5)**k**^3/2^**k**...to ∞) (**k**-1)(**k**-2)(**k**-3)(**k**-4) ***k**^3 x^**k**{at x = 1/2} = (1/24) x^5 * Σ(**k**...%29+C%28**k**-1%2C+**k**-5%29+**k**^3%2F2^**k**I hope...1 Answers · Science & Mathematics · 29/07/2014

**k**(x) = x^2(x^2+16)**k**(4 - √2) = (4 - √2)^2 [(4 - √2)^2 + 16] Remember that (4.... (4 - √2)(4 - √2) = 16 - 8√2 + 2 = 18 - 8√2 So then:**k**(4 - √2) = (4 - √2)^2 [(4 - √2)^2 + 16]**k**(4 - √2) = (18 - 8√2)(18...3 Answers · Science & Mathematics · 16/01/2009

**k**is not c kx^2 - 2x + 1 = 0**k**= a b^2 - 4ac = (-2)^2 - (4)(**k**)(1) = 4 - 4k 4-4k > 0...3**k**^2 - 2k - 3 > 0 Set**k**^2 - 2k - 3 = 0 (**k**- 3)(**k**+ 1) = 0 ==>**k**= 3 or**k**= -1 for**k**^2 - 2k - 3...1 Answers · Science & Mathematics · 15/04/2010

##### Ad

related to: K